611 Safe kids @ home–a survey on chinese families' perspectives on indoor air quality at home. (1st September 2016) - Wang, Fannie; Zhang, Roger; Wang, Mulder; Li, Lisa; Lu, Lydia; Cui, Monica
Abstract : Background: WHO put air pollution is one of the largest environmental risks, but people are more concerned about Outdoor Air Quality (OAQ) but little about Indoor Air Quality (IAQ). People's indoor activities accounts 70% to 90% time of a day. Children may stay longer. This survey is to learn Chinese families perspectives on IAQ, identify knowledge and behaviour gap and collect insights on IAQ promotion. Methods: 10 cities were selected based on geography and year average PM2.5. 100 school-aged children's families participated the survey in each city. Data from 1000 school-aged children was collected through school teachers. Children marked their choices on the questionnaire sheets while teacher reading the questions and choices. Data from 1000 parents was collected online. Parents got an survey invitation with online survey links, they completed the online survey and returned a signed feedback slip to school teacher. Results: 80% of the families consider OAQ as "worse". A limited knowledge of PM 2.5 and its impact, such as 31% of kids have NEVER heard about the word PM 2.5 and 54% of parent do not know the "safety level" of indoor PM 2.5 by WHO. Chemicals, bacteria and viruses are the most concerned ingredients on IAQ at home. An obvious gap between knowing and doing, such as smoking was rated as No. 1 bad for IAQ at home (72%), but 58% of the parents were observed smoking at home. High consensus on improving IAQ at home with 87% families supporting actions on No Smoking, Ventilation, Green-materials for decoration and More greenery. Conclusions: The awareness on IAQ low while the need on IAQ is high. An obvious gap between knowing and doing on smoking at home. Great opportunities to conduct IAQ at home with majority families' support especially actions on No Smoking, Ventilation, Green-materials for decoration and more Greenery.